On the Causal Effect of Fame on Citations - Brogaard, Jonathan; Engelberg, Joseph E.; Eswar, Sapnoti K.; Van Wesep, Edward D. (Management Science, 2024)
Papers published in finance and economics journals whose first authors are famous have more citations than papers whose second or third authors are famous. As a paper ages, its citation rate varies most with variation in the fame of the first author and less so with the fame of second and third authors. Author order is alphabetical, so these patterns are unrelated to underlying quality. The magnitudes we find are large; a three-author paper written by the most prolific author in economics and his two research assistants would increase, on average, its percentile rank by 30 percentage points if the prolific author was first rather than second or third. The effect is especially pronounced in three, rather than two, author papers, suggesting that burying a famous author in the “et al.” reduces citations the most. This paper was accepted by David Sraer, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.00840 .